Development of the computerized system for control of curved surfaces with the help of inductive sensors - Орнатський, Дмитро Петрович; Михалко, Микола Валентинович; Катаєва, Марія Олександрівна (Technology audit and production reserves, 2016)
The article presents the main results of research on the analog interface for remote measurement of linear and angular displacement values inductive sensors with high metrological characteristics. The main purpose of the study is to develop a computerized system for remote measurement and control of curved surfaces using inductive sensors, which provides increased performance and noise immunity. This is achieved by creating a new multifunctional transducers based on iterative integrating converters differentially-current inputs, reduce the effects of stray capacitance electrical cables through the shunting effect is almost zero input resistance and can increase the frequency of the test signal. It is shown that at the same time increases the quality factor of the primary winding IDPTT and reduces the influence of destabilizing factors on the sensitivity of the sensor. The presented system allows to combine in one unit features such as noise suppression, and general strengthening of the normal type and the desired signal. Commutative exchange of information between the sensors allows isolate the generator windings of the sensor from the measuring part of the analog interface, which considerably increases immunity. The algorithm for error correction of the measurement channel using TEDS in terms of non-linearity of the channel and the inter-channel connections is proposed. Results of the study can be implemented in the instrument-making factory in the design and development of new instruments for improving the accuracy and speed of linear and angular measurements using inductive displacement sensor for remote measurements.